Vestibular and oculomotor assessments may increase accuracy of subacute concussion assessment - McDevitt, J.; Appiah-Kubi, K. O.; Tierney, R.; Wright, W. G. (International Journal of Sports Medicine, 2016)
In this study, we collected and analyzed preliminary data for the internal consistency of a new condensed model to assess vestibular and oculomotor impairments following a concussion. We also examined this model`s ability to discriminate concussed athletes from healthy controls. Each participant was tested in a concussion assessment protocol that consisted of the Neurocom`s Sensory Organization Test (SOT), Balance Error Scoring System exam, and a series of 8 vestibular and oculomotor assessments. Of these 10 assessments, only the SOT, near point convergence, and the signs and symptoms (S/S) scores collected following optokinetic stimulation, the horizontal eye saccades test, and the gaze stabilization test were significantly correlated with health status, and were used in further analyses. Multivariate logistic regression for binary outcomes was employed and these beta weights were used to calculate the area under the receiver operating characteristic curve ( area under the curve). The best model supported by our findings suggest that an exam consisting of the 4 SOT sensory ratios, near point convergence, and the optokinetic stimulation signs and symptoms score are sensitive in discriminating concussed athletes from healthy controls (accuracy=98.6%, AUC=0.983). However, an even more parsimonious model consisting of only the optokinetic stimulation and gaze stabilization test S/S scores and near point convergence was found to be a sensitive model for discriminating concussed athletes from healthy controls (accuracy=94.4%, AUC=0.951) without the need for expensive equipment. Although more investigation is needed, these findings will be helpful to health professionals potentially providing them with a sensitive and specific battery of simple vestibular and oculomotor assessments for concussion management.